Cabaran pemeliharaan dan pemuliharaan manuskrip tempatan di Sarawak - A.S., Sabariah; I., Imilia (Persatuan Pustakawan Malaysia, 2013)
Sarawak is a land rich in culture and heritage. There are many different ethnic groups and each of them has a hereditary culture and heritage of its own. Manuscripts are the legacy of the community where they contain aesthetic value in the community. Community uses the manuscript to deliver a range of issues and stories. Thus, conservation measures on existing manuscripts are crucial for the prosperity of future generations. Manuscript preservation is also seen as a necessity for the survival of the local heritage and historical information. This paper discusses how the preservation and conservation activities have been done to the manuscripts in Sarawak. This paper is the result of an observation on the issues of preservation and conservation of manuscripts in the state. This paper also viewed the manuscript as one of the most important resources in preserving the heritage and culture and will be able to empower people within a country.